Politics of giant oil firms: consequences for human rights in Africa - Harshe, Rajen (2003)
The interactions between transnational oil firms, US-led western states and oil rich states in Nigeria, Chad and Angola have certainly facilitated the exploration and extraction of oil as well as the growth of oil revenues. But these revenues have either been deployed to strengthen security - related apparatuses in the context of civil wars or they have been siphoned off by corrupt ruling cliques. A combination of civil wars and bad governance has had extremely negative consequences for human rights in all these countries. - Reproduced.
Keywords: Human rights - Africa; Petroleum resources - Africa; Petroleum resources